Timing But Not Patterns of Recurrence Is Different Between Node-negative and Node-positive Resected Pancreatic Cancer. Issue 2 (August 2020) - Honselmann, Kim C.; Pergolini, Ilaria; Castillo, Carlos Fernandez-del; Deshpande, Vikram; Ting, David; Taylor, Martin S.; Bolm, Louisa; Qadan, Motaz; Wellner, Ulrich; Sandini, Marta; Bausch, Dirk; Warshaw, Andrew L.; et al.
Abstract : Objective: Our aim was to evaluate recurrence patterns of surgically resected PDAC patients with negative (pN0) or positive (pN1) lymph nodes. Summary Background Data: Pancreatic ductal adenocarcinoma (PDAC) is predicted to become the second leading cause of cancer death by 2030. This is mostly due to early local and distant metastasis, even after surgical resection. Knowledge about patterns of recurrence in different patient populations could offer new therapeutic avenues. Methods: Clinicopathologic data were collected for 546 patients who underwent resection of their PDAC between 2005 and 2016 from 2 tertiary university centers. Patients were divided into an upfront resection group (n = 394) and a neoadjuvant group (n = 152). Results: Tumor recurrence was significantly less common in pN0 patients as compared with pN1 patients, (upfront surgery: 55% vs. 77%, P < 0.001 and 64% vs. 78%, P = 0.040 in the neoadjuvant group). In addition, time to recurrence was significantly longer in pN0 versus pN1 patients in the upfront resected patients (median 16 mo pN0 vs. 10 mo pN1 P < 0.001), and the neoadjuvant group (pN0 21 mo vs. 11 mo pN1, P < 0.001). Of the patients who recurred, 62% presented with distant metastases (63% of pN0 and 62% of pN1, P = 0.553), 24% with local disease (27% of pN0 and 23% of pN1, P = 0.672) and 14% with synchronous local and distant disease (10% of pN0 and 15% of pN1, P = 0.292). Similarly, there was no difference in recurrence patterns between pN0 and pN1 in the neoadjuvant group, in which 68% recurred with distant metastases (76% of pN0 and 64% of pN1, P = 0.326) and 18% recurred with local disease (pN0: 22% and pN1: 15%, P = 0.435). Conclusion: Time to recurrence was significantly longer for pN0 patients. However, patterns of recurrence for pN0 vs. pN1 patients were identical. Lymph node status was predictive of time to recurrence, but not location of recurrence.